USULAN PERENCANAAN STRATEGI TEKNOLOGI INFORMASI: STUDI KASUS: PASAR X PT.Y - ALUSYANTI PRIMAWATI (Faktor Exacta, 2012)
The article discusses how to create a management stategy using SWOT analysis method and turn it into TOWS. In the course needed to achieve the vision of marketing strategies in business management, information systems (IS Strategy) and information technology (IT Strategy) should be used. Therefore I am very interested in analyzing how the Pasar X PT. Y is a strong need to define strategies to minimize and manage risks in it. Keyword: Strategy Management, IS Strategy, IT Strategy, BSC.